Hydrocyanic acid, protein concentration, and phytochemical compounds of Pulut and White varieties in young and matured cassava (Manihot esculenta, Crantz) - Idris, Sarah; Shamsudin, Rosnah; Mohd Nor, Mohd Zuhair; Mokhtar, Mohd Noriznan; Abd Gani, Siti Salwa (Universiti Putra Malaysia Press, 2024)
In Malaysia, there is a demand and a promising market for cassava (Manihot esculanta, Crantz) leaves as a supplementary animal feed because of their nutritional value and availability throughout the year. However, cyanide accumulation has been a problem due to its toxicity in animal feed; therefore, finding the best variety with low cyanide, high protein, and phytochemical content can address this issue. The hydrocyanic (HCN) contents were analyzed for two local varieties, White and Pulut cassava, distinguished from leaf shapes and the color of the leaf petioles. Young leaves were identified from the plant’s top leaves, while matured leaves were defined from the plant’s bottom leaves. Two-way ANOVA was conducted to determine the interaction between the maturity and variety of cassava leaves for the cyanide and protein concentrations with Tukey’s multiple ranges to observe the significant difference at p < 0.05. The findings indicated significant differences in the HCN content of cassava leaves between different maturities, while other varieties significantly affected protein concentration. The maturity and variety of cassava leaves showed significant interactions with the HCN content. The young Pulut variety had the highest protein concentration and low HCN content. Thus, it is the best option as an animal feed by reducing its HCN content and maintaining its total phenolic (TPC) and total flavonoid content (TFC). The results imply that variety, as well as maturity, have significant effects on the protein and cyanide concentration of cassava leaves.